Lean Principles Integration with Digital Technologies: A Synergistic Approach to Modern Manufacturing (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The integration of lean principles with digital technologies marks a transformative shift in modern manufacturing and operations management. Lean methodologies focus on reducing waste, optimizing resources, and maximizing value, while digital tools such as IoT, AI, and Big Data Analytics enable real-time monitoring, predictive insights, and automation. This study explores how the combination of these paradigms will enhance operational efficiency, agility, and competitiveness in manufacturing environments. Through an analysis of applications like smart production systems, predictive maintenance, and digital value stream mapping, the research highlights significant benefits, including improved quality, faster decision-making, and reduced downtime. It also examines challenges such as technological complexity, data security, organizational resistance, and the need for workforce upskilling. Emerging trends like Industry 5.0 and human-centric smart factories are discussed, emphasizing the evolving landscape of digitally-driven lean manufacturing. The findings demonstrated that integrating lean principles with digital technologies is no longer optional, but essential for firms aiming to thrive in an increasingly dynamic global market. This synergy represents a strategic pathway towards sustainable operational excellence and innovation in the manufacturing sector.